On‐Demand Tailoring of Optical Branched Flow via Soft Matter Domain Engineering - Yu, Xiao; Fang, Xin‐Yu; Tian, Jing‐Qi; Tang, Xing‐Zhou; Wang, Zi‐Ye; Chen, Jin‐Hui; Lu, Yan‐Qing; Li, Bing‐Xiang (Laser & photonics reviews, 2025)
Soft matter materials, known for their exquisite sensitivity to external stimuli, have facilitated the engineering of intriguing superstructures, driving groundbreaking advancements in photonics devices. However, in‐plane manipulation of optical beams remains challenging, especially in the presence of complex scattering phenomena such as branched flow. Here, the controlled design of branched light flow, beginning with fundamental beam refractions in soft nematic liquid crystals (NLCs), is demonstrated. Leveraging a multistep photoalignment technique, disordered optical potentials are generated by exploiting the intricate inhomogeneity of NLC domain mesostructures. By tuning the density of these domains, the correlation length of disordered potential can be adjusted, thereby enabling control over the branched flow of light. The unconventional intensity statistics and the rapid fidelity decay along propagation are revealed through in‐plane light scattering, illuminating the complex dynamics of light–matter interactions. Furthermore, a phenomenon that transcends the classical understanding of branched flow is uncovered: the emergence of unilateral branches at the boundary of disordered regions of NLCs. This work underscores the unique capabilities of the customizable soft matter platform in shaping the very nature of light transport in planar disordered media and offers a new approach toward novel soft photonics and diffractive optical computing. This work harnesses the capabilities of soft matter platform to customize optical potentials through domain engineering, facilitating in‐plane control of optical beams, from fundamental deflection to complex optical branched flow. By utilizing the photoalignment technique, a tailored design of branched flow is achieved, unveiling the intriguing phenomenon of unilateral branches at the boundaries of designed disordered landscapes.